تطبيق طريقة الغناء حفظ الأمثلة التصرفية لتنمية مهارة كتابة الطلاب المدرسة المتوسطة ميدان التعليم مايانجان جومبانج - Ilmi, Khafidhotul (JURNAL AL-IHDA : Media Ilmiah Bahasa Arab, 2024)
Arabic linguistics makes a great effort to ensure that students understand the material and acquire the Arabic language that has been studied seriously. Students who lack motivation expect the teacher to provide an exciting and innovative educational approach, both in terms of content and process, including teaching methods and means of teaching Arabic.This research aims to (1) How to apply the singing method to develop students' writing ability in middle school education field? (2) What are the obstacles and motivations of the singing method in memorizing behavioral examples to develop students' writing skill in middle school education field? The method used here is the qualitative method, which means that the data collection method is done through direct observation, interviews, and documentation.The results of this research are: (1) It can be seen that the use of songs to improve students' writing skills can be seen through students' interest in learning in class, which helps students understand the material easily. The songs used in teaching are diverse. Sometimes students adopt popular songs at the moment. (2) Internal factors and external factors. Among these factors is interest in learning, which is shown through students' enthusiasm, diligence, and pleasure in following the lessons.